The use of forest resources in central Iberia during the Late Iron Age. Insights from the wood charcoal analysis of Pintia, a Vaccaean oppidum (Journal of Archaeological Science, 2011)
Charred woods may be used to effectively reconstruct past wood acquisition strategies. We used anthracological data from the pre-Roman settlement of Pintia (Padilla de Duero, Valladolid) to examine the use of forest resources at the local scale. Palaeoecological data revealed heterogeneous landscapes in the inland northern meseta with environments that offered diverse sources of wood for the inhabitants of Pintia, one of the ﬁrst cities of inland Iberia. Pines (Pinus pinea/pinaster and Pinus sylvestris/nigra) and both evergreen and deciduous Quercus L. and Juniperus L. were the main taxa identiﬁed as both fuelwood and construction elements, but the assemblages and frequencies of these taxa differed depending on their use. We also examined the potential of models from human ecology by considering the frequency, handling time and the relative technological value of each taxon to model how people gathered wood resources. The results suggest that although local availability affected the forest resources that were used by the Vaccaei people, speciﬁc taxa were positively selected for speciﬁc uses